Estimating the environmental impact of disposable endoscopic equipment and endoscopes. Issue 7 (1st December 2021) - Namburar, Sathvik; von Renteln, Daniel; Damianos, John; Bradish, Lisa; Barrett, Jeanne; Aguilera-Fish, Andres; Cushman-Roisin, Benoit; Pohl, Heiko
Abstract : Objective: Procedure-intense specialties, such as surgery or endoscopy, are a major contributor to the impact of the healthcare sector on the environment. We aimed to measure the amount of waste generated during endoscopic procedures and to understand the impact on waste of changing from reusable to single use endoscopes in the USA. Design: We conducted a 5-day audit (cross-sectional study) of all endoscopies performed at two US academic medical centres with low and a high endoscopy volume (2000 and 13 000 procedures annually, respectively). We calculated the average disposable waste (excluding waste from reprocessing) generated during one endoscopic procedure to estimate waste of all endoscopic procedures generated in the USA annually (18 million). We further estimated the impact of changing from reusable to single-use endoscopes taking reprocessing waste into account. Results: 278 endoscopies were performed for 243 patients. Each endoscopy generated 2.1 kg of disposable waste (46 L volume). 64% of waste was going to the landfill, 28% represented biohazard waste and 9% was recycled. The estimated total waste generated during all endoscopic procedures performed in the USA annually would weigh 38 000 metric tons (equivalent of 25 000 passenger cars) and cover 117 soccer fields to 1 m depth. If all endoscopic procedures were performed with single-use endoscopes and accounting for reprocessing, the net waste mass would increase by 40%. Excluding waste from ancillary supplies, net waste generated from reprocessing and endoscope disposal would quadruple with only using single-use endoscopes. Conclusion: This quantitative assessment of the environmental impact of endoscopic procedures highlights that a large amount of waste is generated from disposable instruments. Transitioning to single-use endoscopes may reduce reprocessing waste but would increase net waste.